Citra Perempuan Urban dalam Novel Wedding Agreement Karya Mia Chuz - Nela Sefriyanti; Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2023)
The main purpose of this research is to describe the image of urban women in the novel Wedding Agreement. This research uses descriptive method. The source of the data in this study is the novel Wedding Agreement by Mia Chuz. The research instrument is the researcher himself as the main instrument using a number of formats, both for data collection and for analyzing data. The data collection technique was carried out by reading the Wedding Agreement novel and inventorying the data into a data inventory format and grouping data related to the image of urban women from the Wedding Agreement novel. The data analysis technique uses content analysis. This research resulted in: (1) the physical image of women found as many as 8 data, including starting from having big eyes with curled eyelashes, neatly sculpted eyebrows, noses not too sharp, but very fit, typical Indonesian olive skin, clean and well-groomed. Body shape is also proportional, not too thin or too fat. (2) psychic imagery in the novel Wedding Agreement found 34 data. The psychic image referred to relates to the psychological or psychological state of the female character in the novel when facing a situation. (3) 23 data regarding women's social image is in the form of an image in the family. Family image as child, family image as wife, family image as sister, family image as daughter-in-law and family image as mother. Each of these roles certainly has a different image. (4) There were 19 data found regarding the role of figures in society, whether as friends, friends, lovers, neighbours, seniors, and bosses. The first image is acting as a boss.